Period–Luminosity Relations for Double-mode δ Sct Stars - Qi Jia; Xiaodian Chen; Shu Wang; Licai Deng; Jianxing Zhang; Qingquan Jiang (The Astrophysical Journal)
Previous studies of the period–luminosity relations (PLRs) of Delta Scuti ( δ Sct) stars have focused on those with a single pulsation mode. However, for δ Sct stars with many different pulsation modes, classifying a single mode is difficult. In this study, an all-sky data set is constructed using double-mode δ Sct stars from the Zwicky Transient Facility and Optical Gravitational Lensing Experiment and is used to determine fundamental (F)-mode and first-overtone (1O)-mode PLRs for eight single bands and six Wesenheit bands. In the W 1 band, the PLR dispersion is about 0.171 mag, and the total zero-point error is 1%. Our results show that to accurately classify the 1O modes of δ Sct stars requires authentication based on multiple modes. Classification based on amplitude alone leads to impure 1O-mode δ Sct stars and significant deviations in the PLRs. We compare the PLRs of the different sequences in the Petersen diagram and find that they are consistent after a strict criterion filtering, suggesting that their evolutionary state is similar. In addition, we find a weak period–metallicity relation for double-mode δ Sct stars, unlike double-mode RR Lyrae stars. As distance tracers, large-amplitude F-mode δ Sct and double-mode δ Sct stars are the most suitable of the δ Sct family.